Biosynthesis and Mapping of ZnO Nanoparticles Using Celery Leaf Extract as Latent Fingerprint Identification - Sari*, Sri Adelila; Nabillah, Luthfi Qori; Putri Br. Siregar, Riri Virzan; Ramadhani, Tiara; Br. Sinulaki, Lesa Octavia; Marbun, Kristin Enjelika (Jurnal IPA & Pembelajaran IPA, 2024)
Latent fingerprint identification is an important aspect in forensic science that helps in revealing criminals. Latent fingerprint visualization methods continue to develop to improve their effectiveness and safety. This study aims to synthesize and map ZnO nanoparticles using celery leaf extract (Apium graveolens L.) and test its effectiveness in latent fingerprint identification. Celery leaf extract is used as a reducing agent and stabilizer in the biosynthesis of ZnO nanoparticles. Characterization of ZnO nanoparticles was carried out using FTIR and SEM-EDS. The characterization results showed that ZnO nanoparticles have a good crystal structure and uniform particle size. Application testing on porous and non-porous surfaces showed that ZnO nanoparticles were able to significantly increase the visibility of latent fingerprints compared to conventional methods. On non-porous surfaces, fingerprint visualization showed clearer results compared to porous surfaces. Thus, this study provides an environmentally friendly and effective solution for latent fingerprint identification in forensic applications, as well as expanding the potential use of natural materials in nanoparticle biosynthesis